Design and Realization of Ohmic and Schottky Interfaces for Oxide Electronics. Issue 2 (12th February 2022) - Zhang, Jie; Pai, Yun-Yi; Lapano, Jason; Mazza, Alessandro R.; Lee, Ho Nyung; Moore, Rob G.; Lawrie, Benjamin J.; Ward, T. Zac; Eres, Gyula; Cooper, Valentino R.; Brahlek, Matthew
Abstract : Ohmic and Schottky Interfaces for Oxide Electronics Complex oxide materials exhibit a wide array of unusual functional properties that can be employed to overcome numerous technological challenges. In article number 2100087, Jie Zhang, Valentino R. Cooper, Matthew Brahlek, and co‐workers demonstrate how a detailed understanding of the alignment of electronic states at oxide‐oxide interfaces can enable designing devices to realize this potential and opens many routes to exploit these fascinating materials.